The Acceptance of Justifications among Shadow IT Users and Nonusers - An Empirical Analysis - Haag, Steffi; Eckhardt, Andreas; Schwarz, Andrew (Information & Management, 2019)
Shadow information technology (IT) usage and justifications, which make shadow IT usage socially acceptable, are major challenges for managers. This study contributes to a better understanding of both the concepts. The results show significant differences between shadow IT users and nonusers in the degree to which they accept justifications in light of IT constraints, in particular, in the situational factors driving this acceptance. While perceived noncompliance of others influences shadow IT users' acceptance of justifications, nonusers accept justifications of noncompliant fellows if they expect benefits of shadow IT usage. New implications for managers are provided with the aim of reducing shadow IT usage.
CRIS-Team WoS Importer:2019-07-12
Keywords: JustificationsShadow ITNeutralizationIT policy complianceNoncompliance